Sensory preference and detection threshold for salt taste among undergraduate students, Health Campus, Universiti Sains Malaysia - Razak, Nurul Husna Abdul (Pusat Pengajian Sains Kesihatan, 2017)
Salt is one of the human’s essential food seasonings. Most dietary sodium is consumed as common salt (sodium chloride). About 90% of salt is largely added in food processing, in restaurant food, in sauces and cooking. However, high consumption of salt is highly related with several health problems such as hypertension, stroke, cardiovascular disease and obesity. The purpose of this study is to determine the preference and detection threshold for saltiness among Malay, Chinese and Indian students of Universiti Sains Malaysia, Health Campus. Detection threshold for saltiness was determined by using the three-alternative forced-choice (3-AFC) while the preference for saltiness was determined by using the Hedonic Test. For detection threshold, the value of BET group for Malay students was 1.564mM, 1.1854mM for Chinese students and 0.8988mM for Indian students. These results indicated that Malay students have the highest BET group value for detection threshold compared to other ethnics. Across genders, male students from Indian ethnicity showed the highest detection threshold to sodium (1.727mM). Meanwhile, Malay female students had the highest detection threshold (2.257mM) as compared to Chinese and Indian. For the preference for saltiness, Malay students had the highest preference with sodium concentration of 0.5%w/v. Chinese students preferred sodium concentration of 0.375%w/v the most while Indian students had the highest preference of sodium, which was at concentration 0.375%v/w. These results indicated that Malay preferred saltier food compared to Chinese and Indian. Across genders, Malay and Chinese male students had higher preference for saltiness compared to females. Meanwhile, among Indian students, males only had higher preference for the first three lowest concentrations. No relationship was found between detection threshold and preference for saltiness among Malay, Chinese and Indian students. In conclusion, detection threshold for saltiness, preference for saltiness and relationship between them were determined in this study.